Acute respiratory infections in young Ethiopian children - Harris RA (Dove Medical Press, 2015)
Rebecca Arden HarrisDepartment of Family and Social Medicine, Montefiore Medical Center, Albert Einstein College of Medicine, Bronx, NY, USAThe identification of risk factors for acute respiratory infections (ARI) is crucial for designing interventions to both minimize transmission and augment the immune response, particularly in Sub-Saharan Africa where poverty-related ARI is still a major cause of preventable death in young children.1 I therefore read with interest Geberetsadik et al’s recent study of the factors associated with ARI in Ethiopian children.2 Their study uses nationally representative data on households and individuals to build a model of the social, demographic, and anthropometric determinants of ARI. A precise understanding of their model, however, requires clarification of several items in their paper.View original paper by Geberetsadik et al.